2016
DOI: 10.1016/j.soilbio.2015.10.017
|View full text |Cite
|
Sign up to set email alerts
|

The decomposition of ectomycorrhizal fungal necromass

Abstract: a b s t r a c tThe turnover of ectomycorrhizal (EM) fungal biomass represents a significant input into forest carbon (C) and nutrient cycles. Given the size of these fluxes, understanding the factors that control the decomposition of this necromass will greatly improve understanding of C and nutrient cycling in ecosystems. Recent research has highlighted the considerable variation in the decomposition rates of EM fungal necromass, and patterns from this research are beginning to emerge. In this article we revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
109
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(120 citation statements)
references
References 166 publications
4
109
0
Order By: Relevance
“…In fact, concentrations of chitin were associated with faster rates of decomposition (Fernandez and Koide 2012). These findings have been supported by Drigo et al (2012), Zeglin et al (2013) and Russell (2014), who report rapid declines in chitin concentrations within decomposing fungal tissues (Fernandez et al 2016).…”
Section: Explanations For Slow Decomposition Of Lower Order Rootsmentioning
confidence: 67%
See 2 more Smart Citations
“…In fact, concentrations of chitin were associated with faster rates of decomposition (Fernandez and Koide 2012). These findings have been supported by Drigo et al (2012), Zeglin et al (2013) and Russell (2014), who report rapid declines in chitin concentrations within decomposing fungal tissues (Fernandez et al 2016).…”
Section: Explanations For Slow Decomposition Of Lower Order Rootsmentioning
confidence: 67%
“…For instance, AM fungi produce the hydrophobic glycoprotein, glomalin which may aid in waterproofing hyphae as they transport nutrients (Rilling et al 2002;Fernandez et al 2016). Like glomalin, ECM fungi produce hydrophobic proteins or hydrophobins that coat the outside of cell walls, making hyphae un-wettable (Fernandez et al 2016). The hydrophobic nature of these fungal proteins also likely retards enzymatic decomposition.…”
Section: Explanations For Slow Decomposition Of Lower Order Rootsmentioning
confidence: 99%
See 1 more Smart Citation
“…Melanin allows fungi to tolerate environmental stress and makes their biomass recalcitrant to degradation (Fernandez et al ., ). The analyses of five genes linked to melanin biosynthesis (Methods S1) showed that two of them ( arp1 – scytalone dehydratase and abr1 – brown 1) were significantly enriched in ERM fungi compared with fungi with different ecological strategies (Table S9).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, Ascomycota mycelia are more likely to leave a large proportion of a fungal necromass that serves to store carbon in boreal soil (6, 9). Our results showed that the abundance of mycorrhizal fungi of the phylum Ascomycota increased with higher TC contents in the Sasa -intact plot (Fig.…”
Section: Discussionmentioning
confidence: 99%